บทบาทและวาทะของผู้นำในธุรกิจประกันชีวิตในประเทศไทย - โชคชัย อัครวราวงศ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2001)
To investigate factors influencing life insurance agents decisions to pursure their career. In addition, the study focused on exploring whether or not and how life insurance business leaders roles and speeches had affected the life insurance agents working and life objectives in their career. Questionnaire and interview data (n=150) were collected from the top three famous life insurance companies in Thailand. The study results indicated that: 1. Major factors which influenced life insurance agents decisions to pursue their career were remuneration, autonomy, opportunity in work promotion and enhancement, opportunity to travel aboard, work and life security, involvement in supporting social security, and social acceptance. 2. Life insurance business leaders personal attributes (i.e., good personality, good morality, and effective persuasive communication skills) had strong influences on their life insurance agents positive attitudes toward their career. 3. Life insurance business leaders speeches which had influenced on their life insurance agents dealt with the following 4 categories: 1) speeches related to the belief in human potentials, 2) speeches relevant to the power of human thought, 3) speeches concerning human s mind and self-control, and 4) speeches being quoted from great philosophers.